The End of Multilateralism? Rising Regional Trade Agreements, Trade Wars, and The Future of the International Trading System - Hekim, Derya (European Scientific Journal, ESJ, 2026)
The multilateral trading system faces an existential crisis driven by three mutually reinforcing dynamics: the structural failings and deliberate paralysis of the World Trade Organization (WTO), most acutely manifested in the Appellate Body’s incapacitation since December 2019; the exponential proliferation of regional trade agreements (RTAs); and two waves of unprecedented trade wars under the Trump administration in 2018–2020 and 2025–2026. While substantial scholarship addresses each phenomenon in isolation, no existing study integrates the three within a single comparative analytical framework that also encompasses the second Trump trade war and the February 2026 US Supreme Court ruling on the IEEPA tariffs. This study fills that gap through an integrated comparative analytical framework drawing on terms-of-trade theory, the deep-agreements literature, and the welfare economics of trade wars. The analysis is supported by quantitative tariff series, comparative tables of the two trade wars and three governance scenarios, and a focused case study of critical mineral and technology export controls. Four conclusions follow: the WTO crisis is structural rather than cyclical; RTA welfare effects depend on agreement depth, not on regionalism per se; a tiered architecture combining deep RTAs, a residual WTO baseline, and bilateral managed trade is the most plausible trajectory; and critical mineral and technology export controls constitute an emerging governance gap that no existing framework adequately disciplines.